Geochemistry of komatiites and basalts in Archean greenstone belts of Russian Karelia with emphasis on platinum-group elements - Guo, Fang-Fang; Svetov, Sergei; Maier, Wolfgang D.; Hanski, Eero; Yang, Sheng-Hong; Rybnikova, Zoya (Mineralium Deposita, 2020)
Archean komatiites form an important host rock for Ni-Cu sulfide deposits in the world. In this study, we examined Archean komatiites and komatiitic basalts from four areas in the Vedlozero-Segozero greenstone belt and two areas in the Tikshozero greenstone belt, Russian Karelia, to constrain their Ni-Cu sulfide mineralization potential using chalcophile element geochemistry. The platinum-group element (PGE) concentrations in these Munro-type komatiitic rocks are at a level of other similar S-undersaturated komatiites and komatiitic basalts globally, with Pt and Pd concentrations in the range of 5–20 ppb and Pd/Ir varying from < 10 (komatiites) to > 15 (komatiitic basalts and basalts). Generally, the metals of the iridium-group elements (IPGEs; Ir, Ru, Os) show a compatible behavior, decreasing in abundance with decreasing MgO, whereas the metals of the palladium group (PPGEs; Pt, Pd, Rh) exhibit an incompatible behavior. The poor correlation between Ir and MgO suggests that olivine fractional crystallization is not the main control on the behavior of IPGE. In contrast, Ir, Ru, and Os show positive correlations with Cr, which is consistent with the compatible behavior of IPGEs in chromite or during the co-precipitation of chromite and platinum-group minerals (PGMs). Palladium, Cu, and Au have been variably mobile during alteration and metamorphism whereas Pt appears to have been less mobile. Some samples from the Khizovaara area show low (Pt/Ti)N ratios, low Ni, and high La/Sm and La/Nb, suggesting localized sulfide saturation in response to crustal contamination. However, the potential of the Russian Karelian greenstone belts for Ni-Cu sulfide mineralization is considered relatively low because most samples show neither enrichment nor depletion of chalcophile elements, and the paucity of dynamic lava channel environments, as indicated by the scarcity of olivine-rich adcumulates. In addition, there appears to be a lack of exposed sulfidic sedimentary rocks in the region.